Simulasi Produksi Neutron pada LINAC Radioterapi menggunakan metode Monte Carlo FLUKA-FLAIR - Ramdani, Ridwan; Sutrisna, Irma Wati; Syaja'ah, Khoerun Nisa; Aliah, Hasniah (Universitas Sultan Ageng Tirtayasa, 2023)
The use of high-energy photon beams in radiotherapy aims to increase the effectiveness of the radiation beam so that it can reach tumors that are deeper than the surface of the skin. However, linac aircraft operated above 8 MV can cause photonuclear interactions. Neutrons, which are highly avoided in medical physics, can be generated from the interaction of high-energy photons with materials with high atomic numbers (Z) in linac heads. The study focused on simulating the production of linac 10 MV aircraft contaminant neutrons using Fluka-Flair software based on the Monte Carlo method to find out where the contaminant neutrons come from and their dose contribution to the water phantom. The simulated linac aircraft is a linac head consisting of target components, primary collimator, Flattening filter, ion chamber, Secondary Collimator, and Phantom. The simulation results show that neutrons are generated at the target component, primary collimator, Flattening filter, ion chamber, secondary collimator, and water phantom. Tungsten is the target material with the most excellent 55,08% neutron fluence due to its highest atomic number, Primary Collimator 23,45%, Flattening Filter 10,67%, Ion Chamber 7,58%, Secondary Collimator 3,07% and Phantom 0,15 %.